Faktor Penghambat Berkembangnya Bisnis dari Badan Usaha Milik Desa di Kabupaten Sumba Timur - Kelen, Lusianus Heronimus Sinyo; Bima, Stevvileny Angu (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research objective: This research aims to determine the inhibiting factors for the business development of BUM Desa in East Sumba Regency, East Nusa Tenggara Province. Research method: The research method used was grounded theory and employed a qualitative approach to bring a phenomenon into theory. The study was conducted by collecting data from enumerators who were Unkriswina Sumba students. The collected data comprised 64 informants from 19 BUM Desa spread over 14 sub-districts in East Sumba Regency. Results: There are six factors causing obstacles to the business of BUM Desa in East Sumba Regency from developing, namely: 1) Low readiness of Human Resources (HR) in managing BUM Desa businesses, 2) low public awareness to support the running of BUM Desa, 3 ) management or financial management that is still lacking, 4) low planning analysis before starting a business, 5) poor oversight and coordination functions from the village government to BUM Desa administrators, and 6) lack of BUM Desa infrastructure. The novelty of research: a research approach based on a grounded theory approach to identify the factors causing the BUM Desa activities not to work based on the root of the problem and the phenomenon, then from this phenomenon, a theory is formed, which is also known as